Technology Adoption in Education-Based Business Services - Lusianus Kusdibyo; Hewage Lakshi Krishani Perera; Gundur Leo (Jurnal Internasional Penelitian Bisnis Terapan, 2019)
The objectives of this study are two folds. Firstly is to identify the advantages and disadvantages factors of electronic learning’s adoption. Secondly is to measure the influence of innovation adoption components toward users’ attitude in using electronic learning. A mixed method of study was carried out in response to the research’s objectives. The qualitative approach was conducted by means of interviewing 25 participants of users to identify e-learning advantages and disadvantages. The quantitative approach was used to test the hypotheses. A questionnaire was distributed to 313 e-learning system users. The results show that the three advantages and disadvantages of e-learning adoption factors were formed. SEM-Smart PLS was used to test the hypothetical relationships. The results indicate that three dimensions of innovation diffusion significantly influenced the attitude toward e-learning, while two dimensions were not significant. The findings suggest that education-based business services should use the advantages factors and influential dimensions to promote their teaching-learning services delivery and eliminate weaknesses and insignificant dimensions.